Моделирование и оптимизация процессов выпаривания солевых растворов - Фокин, Виталий Сергеевич; Павлова, Виктория Геннадьевна; Данилов, Д. Ю. (НТУ "ХПИ", 2011)
A study of solutions evaporation processes is a difficult task which requires complex approach. Considering this problem it is necessary to take into account a number of questions, related to intercommunication of processes in the evaporator. In turn evaporator is rather difficult system of closed circuit type. Processes which take place in different areas of evaporator are closely associated inter se and give a cross-coupling on each other. In the article the analysis of processes in various areas of evaporator is presented and the connection between them is shown.
Keywords: кристаллизация солей; интенсификация процессов циркуляции, теплообмена и кристаллизации; диффузионная модель; уравнение теплового баланса; молекулярная масса растворителя и выделившейся соли